Effects of exposure to high potassium concentration on the longitudinal muscle-myenteric plexus preparation from guinea-pig. Issue 2 (February 1986) - Aleixandre, M. A.; Ayala, E.; Garcia de Jalón, P.
Abstract : The effect of potassium on the longitudinal muscle-myenteric plexus (LM-MP) preparation from guinea-pig was studied. The strips were exposed to elevated K + (30 m M, 60 m M, 90 m M, 120 m M or 150 m M ). A phasic contraction of the LM-MP was caused by 10m M K + or 15 m M K + followed by an increase of the contractile activity probably due to the increase in acetylcholine release. A higher molarity of K + produces more marked depolarization in the LM-MP and above 22m M K + tetanizing effects were observed. We attempted to demonstrate that opiate-like material could be released when the tissue was exposed to more than 30 m M K + even though several different neurotransmitters could be liberated by elevated K + molarities.